Uncertainty, misallocation and the life-cycle growth of firms - Eero Mäkynen; Oskari Vähämaa (Aboa Centre for Economics (ACE), 2021)
We develop a measure of static misallocation that separates uncertainty from misallocation generated by tax-like distortions. In the Finnish firm-level data, uncertainty accounts for the majority of ex post misallocation and explains a strong decreasing age-dependent trend in it. To understand these observations, we set up a life-cycle model of firm growth where new firms have to learn their productivity. We match our model with the salient features of the data and show that our model implies idiosyncratic distortions, in line with our accounting approach. According to our quantitative results, uncertainty suppresses output by 38%, while misallocation has a 26% negative effect on output.
Keywords: D24; E23; L11; O47; 330; firm dynamics; uncertainty; misallocation